SEMANTIC AND STRUCTURAL ADAPTATION OF FASHION-RELATED LOANWORDS IN CONTEMPORARY ENGLISH - Boymurodova Barno Elmurod qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the semantic and structural mechanisms of adaptation of borrowed words related to the fashion industry in modern English. The work is done in the IMRAD style and is based on the theoretical propositions of W. Weinreich, E. Hougen, L. Bloomfield, A. Smirnitsky, S. Ulman and other researchers of contact linguistics. The "Results and Discussion" section analyzes in detail the processes of semantic narrowing, expansion, metaphorization and re-evaluation of meaning, as well as phonological, morphological and syntactic adaptation. Special attention is paid to the influence of socio-cultural factors, including the prestige of the donor language, the role of the media, the professionalization of fashionable discourse and cultural identity. The article can serve as a theoretical basis for further research in the field of English lexicology and sociolinguistics.